Food labelling as an instrument for achieving the objectives of food law: selected issues - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2021)
The aim of this paper is to determine how the objectives of food law are achieved through the regulation on the labelling of food and to examine the relationship occurring between the achievement of the general objectives of food law and the particular objectives of the food labelling regulation. Having outlined the particular objectives of food law first, the author assigned to them general and detailed regulations governing the labelling of food and aimed at the achievement of particular objectives. These regulations are subsequently discussed. Their analysis leads to a conclusion that two of the objectives of food law, i.e. the protection of health and life and of consumers’ interests and the reliability of trade are largely achieved by regulations shaping the obligatory scope of information that must be provided on the label. Additionally, consumer protection is ensured by labelling rules, the basic principle of which is not to mislead consumers. However, under the current legal framework, environmental and animal welfare protection is only covered to a small extent only and only by detailed regulations. Understanding consumers’ expectations regarding environmental and animal welfare information, the author proposes to adopt a framework regulation that would define the rules for the use of environmental claims. Such a regulation would be similar to the regulation of nutrition and health claims.